2020
DOI: 10.1074/jbc.ra120.013050
|View full text |Cite
|
Sign up to set email alerts
|

A variant of human growth differentiation factor-9 that improves oocyte developmental competence

Abstract: Growth differentiation factor-9 (GDF9) and bone morphogenetic protein-15 (BMP15) are co-expressed exclusively in oocytes throughout most of folliculogenesis and play central roles in controlling ovarian physiology. Although both growth factors exist as homodimers, recent evidence indicates that GDF9 and BMP15 can also heterodimerize to form the potent growth factor cumulin. Within the cumulin complex, BMP15 “activates” latent GDF9, enabling potent signaling in granulosa cells via type I receptors (i.e. activin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 53 publications
(73 reference statements)
2
34
0
Order By: Relevance
“…As obesity led to an increase in the number of atretic follicles, we wondered if this increase was induced by the abnormal expressions of the genes BMP4, GDF9, or LHX8 that play key roles during ovarian follicular development (Fu et al, 2017;Liu et al, 2017;Stocker et al, 2020). Our results demonstrated that there were no significant differences in their mRNA expression levels among the three mice groups, suggesting that the increased number of atretic follicles was not caused by abnormal BMP, GDF9, and LHX8 gene expression.…”
Section: Discussionmentioning
confidence: 70%
“…As obesity led to an increase in the number of atretic follicles, we wondered if this increase was induced by the abnormal expressions of the genes BMP4, GDF9, or LHX8 that play key roles during ovarian follicular development (Fu et al, 2017;Liu et al, 2017;Stocker et al, 2020). Our results demonstrated that there were no significant differences in their mRNA expression levels among the three mice groups, suggesting that the increased number of atretic follicles was not caused by abnormal BMP, GDF9, and LHX8 gene expression.…”
Section: Discussionmentioning
confidence: 70%
“…However, to date, it is still unknown whether this cooperation is generated by GDF9 and BMP15 homodimers separately or by the GDF9/BMP15 heterodimer. Interestingly, in vitro studies have shown that the recombinant human GDF9/BMP15 heterodimer potently activates Smad2/3 signalling in mammalian granulosa cells and improve embryo development during oocyte in vitro maturation compared to human GDF9 and BMP15 homodimers ( 29 , 30 , 59 ). However, our current findings indicate similar intrafollicular concentrations of the GDF9/BMP15 heterodimer and BMP15 in small antral follicles, suggesting that only a minor proportion of the total GDF9 would potentially form a heterodimer with BMP15 in vivo, and that GDF9 performs actions on its own as a homodimer.…”
Section: Discussionmentioning
confidence: 99%
“…GDF9 plays an important role in controlling ovarian physiology and enhancing oocyte developmental competence [ 41 ]. The GDF9 mutation can affect the fertility and sterility by producing different effects on number of follicles and oocyte in ewes [ 1 ].…”
Section: Discussionmentioning
confidence: 99%